KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA SELAMA MASA PANDEMI COVID-19 - Siti Kustinah (Komitmen: Jurnal Ilmiah Manajemen, 2021)
Various types of businesses in Indonesia experienced a decline in their financial performance as a result of the Covid-19 pandemic which had a negative effect on the economy. The purpose of carrying out this research is to be able to see how the effects of the Covid-19 pandemic on the financial performance of several companies listed on the Indonesia Stock Exchange. The research sample used was 214 companies with data analysis using the Wilcoxon Signed-Rank test. The research then succeeded in finding that there was an increase in the leverage ratio and the short-term activity ratio. However, during the pandemic, it was found that there was a decline in the liquidity ratio and profitability ratio. This increase and decrease changed before the pandemic to the current pandemic.KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA SELAMA MASA PANDEMI COVID-19